Rhodiola pre-conditioning reduces exhaustive exercise-induced myocardial injury of insulin resistant mice - You, Baiyang; Cheng, Jing; Dun, Yaoshan; Ripley-Gonzalez, Jeffrey W.; Liu, Jie; Li, Dezhao; Fu, Siqian; Hong, Chuangxiong; Liu, Suixin (Scientific reports, 2022)
Myocardial injury reduction and recovery under acute cardiac stress are adversely impacted by insulin resistance (IR). We previously demonstrated that Rhodiola improved cardiac anti-stress capacity in mice. Thus, this study focuses on the preventive efficacy of Rhodiola on exhaustive exercise (EE)-induced myocardial injury of IR mice. An 8-week high-fat diet (HFD) model of IR mice was established. Rhodiola was administrated by garaging. After the 8-week intervention, half of the mice performed EE to simulate acute cardiac stress, and determine myocardial injury; The remaining mice were sacrificed following fasting to assess metabolic disorder. We found myocardial injury induced by EE in IR mice was worse and was alleviated by Rhodiola pre-conditioning. Further, the nuclear factor erythroid 2-related factor 2 (Nrf2)-related antioxidant system was impaired by HFD, while mitochondrial dynamic fusion and fission were activated by HFD as a physiological protective compensation. The Rhodiola administration rescued Nrf2 impairment and further facilitated mitochondrial fusion and fission. All these results indicate that Rhodiola is a potential treatment for the prevention of cardiac events in type 2 diabetes mellitus and metabolic syndrome patients, and the Nrf2-related antioxidant activity and mitochondrial dynamics are the proposed mechanisms.